2015
DOI: 10.4103/2141-9248.149763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analytical errors in a clinical chemistry laboratory: A 3 year experience

Abstract: Background:Proficient laboratory service is the cornerstone of modern healthcare systems and has an impact on over 70% of medical decisions on admission, discharge, and medications. In recent years, there is an increasing awareness of the importance of errors in laboratory practice and their possible negative impact on patient outcomes.Aim:We retrospectively analyzed data spanning a period of 3 years on analytical errors observed in our laboratory. The data covered errors over the whole testing cycle including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 11 publications
4
30
2
Order By: Relevance
“…In addition, these published analytical error rates for molecular genetic tests are quite comparable to those found for other more automated diagnostic analytes in laboratory medicine, with well-documented analytical error rates ranging from 0.01 to 5%. [30][31][32][33][34][35][36] Prior publications have also documented findings analogous to this study concerning a higher variability in interpretive (compared with analytical) performance, with interpretive accuracy rates ranging from 92.5% for BRCA1/2 (ref. 25) to 99.7% for familial dysautonomia.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, these published analytical error rates for molecular genetic tests are quite comparable to those found for other more automated diagnostic analytes in laboratory medicine, with well-documented analytical error rates ranging from 0.01 to 5%. [30][31][32][33][34][35][36] Prior publications have also documented findings analogous to this study concerning a higher variability in interpretive (compared with analytical) performance, with interpretive accuracy rates ranging from 92.5% for BRCA1/2 (ref. 25) to 99.7% for familial dysautonomia.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the International Federation of Clinical Chemistry and Laboratory Medicine Working Group for Laboratory Errors and Patient Safety (IFCC-WG-LEPS) organized a series of quality markers on the pre-analytical phase to highlight pre-analytical phase errors [4]. The most common extra-analytical errors include inappropriateness of test order, patient identification error, timing errors in sampling and preparation, hemolytic and lipemic blood samples, inappropriate transport, and inadequate and inappropriate sample collection tubes [5] (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…In general, the frequency of errors in the preanalytical phase and postanalytical phase comprise the vast majority (Bonini et al 2002;Sonntag 2009). Errors within the analytical phase are usually few, and results indicated that the number of errors within the analytical phase has continued to decrease over the last decade (Plebani 2006(Plebani , 2010Sakyi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Some examples of analytical errors include equipment malfunction, procedures (i.e., standard operating procedures and assay instructions) not followed, undetected failure of quality control, sample mixups, and test interference. In many studies of total testing errors, analytical errors are often <10% and their frequency is decreasing due to standardization of laboratory procedures and assays, automation within the clinical pathology laboratory, and advances in technology (Plebani 2006(Plebani , 2010Sakyi et al 2015). However, in human medicine, immunoassays remain a prime concern for analytical errors due to the presence of heterophilic antibodies, antianimal antibodies, and anti-idiotype antibodies within patient sera.…”
Section: Resultsmentioning
confidence: 99%